Effects of the Natural Flavonoid Quercetin on Arenavirus Junín Infection - Alvarez de Lauro, Aaron Ezequiel (2023)
There is no specific chemotherapy approved for the treatment of pathogenic arenaviruses that cause severe hemorrhagic fever (HF) in the population of endemic regions in America and Africa. The present study reports the effects of the natural flavonoid quercetin (QUER) on the infection of A549 and Vero cells with Junín virus (JUNV), agent of the Argentine HF. By infectivity assays, a very effective dose-dependent reduction of JUNV multiplication was shown by cell pretreatment at 2–6 h prior to the infection at non-cytotoxic concentrations, with 50% effective concentration values in the range of 6.1–7.5 µg/mL. QUER was also active by post-infection treatment but with minor efficacy. Mechanistic studies indicated that QUER mainly affected the early steps of virus adsorption and internalization in the multiplication cycle of JUNV. Treatment with QUER blocked the phosphorylation of Akt without changes in the total protein expression, detected by Western blot, and the consequent perturbation of the PI3K/Akt pathway was also associated with the fluorescence redistribution from membrane to cytoplasm of TfR1, the cell receptor recognized by JUNV. Then, it appears that the cellular antiviral state, induced by QUER treatment, leads to the prevention of JUNV entry into the cell.